Profile and outcomes of in-hospital cardiac arrest in a paediatric emergency department - Muhammad Irfan Habib; Murtaza Gova; Huba Atiq (Journal of the Pakistan Medical Association, 2021)
Objective: To determine the profile and outcome of patients for in-hospital cardiac arrest (IHCA) in an emergency department (ED). Methods: It is a retrospective study of one year from Jan – Dec’ 2017 for patients who suffered cardiac arrest during their stay in emergency department of National Institute of Child Health (NICH), Karachi, Pakistan. Data was seen for IHCA only and their outcomes including rate of ROSC (Return of Spontaneous Circulation). Patients with out of hospital cardiac arrest were excluded. Results: Total number of children landed in critical conditions were 19,385. In-Hospital Cardiac Arrest were noted in 935 (5%) cases during the study period. ROSC was achieved in 568 (61%). Males were 556 (59%). Infants (<12 months of age) were among the top who suffered in-hospital cardiac arrest they were 719 (77%). The outcome of those who suffered cardiac arrest that 505 (54%) of them survived till emergency room management before disposal to the high level of care. Just 140 cases (15%) landed in emergency department through ambulance and the outcomes were better who landed through ambulance. Conclusion: More than half of the patients achieved ROSC after in-hospital cardiac arrest and half of them stabilized till final disposal from Emergency department. Utilization of ambulance service seems very low. Most common age group was infant. Continuous...